On Bernstein Polynomials Method to the System of Abel Integral Equations - A. Jafarian; S. Measoomy Nia; Alireza K. Golmankhaneh; D. Baleanu (Abstract and Applied Analysis)
This paper deals with a new implementation of the Bernstein polynomials method to the numerical solution of a special kind of singular system. For this aim, first the truncated Bernstein series polynomials of the solution functions are substituted in the given problem. Using some properties of these polynomials, the solution of the problem is reduced to solve a linear system of algebraic equations. In order to confirm the reliability and accuracy of the proposed method, some weakly Abel integral equations systems with comparisons are solved in detail as numerical examples.